Fluoxetine-related ecchymosis treated with venlafaxine: a case report - Hakan Karaş; Taner Yılmaz (Psychiatry and Clinical Psychopharmacology, 2017)
Selective serotonin reuptake inhibitors (SSRIs) are known to have a relatively favourable side effect profile. In recent years, there has been an emphasis on the risk of upper gastrointestinal bleeding in patients taking SSRI antidepressants. Although they may have some effects on coagulation profile, ecchymosis is a rare clinical manifestation of these effects. Here, we report a 25-year-old female patient who was diagnosed with major depressive disorder and manifested spontaneous ecchymoses on her legs rapidly following fluoxetine use. Her complete blood cell count, prothrombin time, partial thromboplastin time, bleeding time, and other hematological screening tests were within normal limits. After discontinuation of fluoxetine, her ecchymoses were resolved in two weeks. Ecchymosis did not recur after fluoxetine was discontinued, and the patient was switched to venlafaxine.